2020
DOI: 10.1155/2020/2508283
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Rifampicin Resistance Associated with Rural Residence and Very Low Bacillary Load among TB/HIV-Coinfected Patients at the National Tuberculosis Treatment Center in Uganda

Abstract: Background. Rifampicin resistance (RR) is associated with mortality among tuberculosis (TB) patients coinfected with HIV. We compared the prevalence of RR among TB patients with and without HIV coinfection at the National Tuberculosis Treatment Center (NTTC) in Uganda, a TB/HIV high burdened country. We further determined associations of RR among TB/HIV-coinfected patients. Methods. In this secondary analysis, we included adult (≥18 years) bacteriologically confirmed TB patients that were enrolled in a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…Studies have shown that previous TB drug exposure, especially in inadequate or inappropriate doses, can result in an increased risk of developing mono-drug or multidrugresistant tuberculosis [25][26][27][28]. The findings of this study of higher prevalence of MTB drug resistance among previously treated patients is consistent with findings of other Ugandan studies [25,29,30] and other neighbouring countries [4,31,32]. These high levels of drug resistance among previously treated patients raise concerns about TB treatment compliance and the successful application of drug resistance preventive measures such as directly observed…”
Section: Discussionsupporting
confidence: 87%
“…Studies have shown that previous TB drug exposure, especially in inadequate or inappropriate doses, can result in an increased risk of developing mono-drug or multidrugresistant tuberculosis [25][26][27][28]. The findings of this study of higher prevalence of MTB drug resistance among previously treated patients is consistent with findings of other Ugandan studies [25,29,30] and other neighbouring countries [4,31,32]. These high levels of drug resistance among previously treated patients raise concerns about TB treatment compliance and the successful application of drug resistance preventive measures such as directly observed…”
Section: Discussionsupporting
confidence: 87%
“…HIV positive status is statistically significantly associated with MDR - TB, the study findings indicated that 26.9% of HIV positives had MDR-TB. This is agreeing with a Ugandan study 16 , which found out that the prevalence of MDR-TB was 32.4% among HIV/TB co-infected patients. Another study 14 reported that 40% - 70% of HIV patients in Ethiopia are co-infected with MDR-TB.…”
Section: Discussionsupporting
confidence: 92%
“…Identifying gender differences can guide implementation of gender-specific interventions to improve DRTB treatment outcomes. Uganda is a TB/HIV high burdened country, and 52–62% of patients with DRTB are co-infected with HIV [ 18 , 19 ]. In this study, we compared socio-demographic and clinical characteristics and treatment outcomes of DRTB/HIV co-infected men and women in Uganda, drawn from a large countrywide retrospective cohort [ 20 ].…”
Section: Introductionmentioning
confidence: 99%